Urgensi PPAT dalam Proses Jual Beli Tanah dan Bangunan dalam Tinjauan Yuridis - Prasetyo, Muhammad Arif (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2023)
When making a deed, the Land Deed Making Officer (PPAT) is obliged to ensure that the BPHTB payment owed has been paid in full by the Taxpayer. For this reason, it is necessary to study the role of PPAT in the imposition of BPHTB in the transfer of rights to land and buildings, the legal consequences of the imposition of BPHTB in deeds of sale and purchase of land and buildings and the mechanism for the imposition of BPHTB in deeds of sale and purchase. The type of research used in writing this is normative juridical, which is descriptive analysis. The data collection technique used is library research. The role of PPAT in the Imposition of BPHTB in the Transfer of Rights to Land and Buildings is to convey the necessary information relating to the process of imposition of BPHTB in the imposition of BPHTB tax on the transfer of rights to land and buildings. The legal consequence of the imposition of BPHTB in the Deed of Sale and Purchase of Land and Buildings is that the Deed of Sale and Purchase cannot be executed before the BPHTB in the sale and purchase transition transaction has not been paid by the taxpayer, which also results in legal certainty in the transition.